DESAIN ANIMASI 2D PENGETAHUAN DASAR BAHAYA NARKOBA BAGI PEMUDA DENGAN METODE PTP PADA DISPORAPAR KENDAL - Setiyo Prihatmoko; Sumaryanto Sumaryanto; Raffida Zakki H (STEKOM PRESS, 2023)
Drugs have become a serious problem in Indonesia. Because in every region in Indonesia there is no area free of drug abuse. One of the causes of drug abuse is mistakes in association and shortcuts to escape from the burden of thoughts. However, they do not realize the impact of drug abuse, which can be addictive and have an effect on health. Therefore, each of us has an obligation to disseminate information about the dangers of drug abuse. So that our family, friends and loved ones don't fall into the trap of using drugs. This study aims to: (1). Design and create 2D animation of the dangers of drug abuse (2). Design and create 2D animations in the form of animated videos using the PTP method that are attractive and understandable to the public. The research method used in this study is a Research and Development (RnD) product. The effectiveness and communicativeness of animated videos can be seen from the results of calculating the questionnaire from 35 respondents who gave very positive responses, namely valid and reliable